Impact of agricultural infrastructure development on inequality and optimization equality of farmers’ income in Indonesia-Timor Leste Border Area - Taena, Werenfridus; Sipayung, Boanerges Putra; Blegur, Fried Markus Allung; Klau, Anggelina Delviana (Asian Journal of Agriculture and Rural Development, 2023)
This research aims to analyze income inequality and the factors determining inequality, as well as the allocation of land resources that optimize income distribution. The research is a continuation of previous research that found production and income growth as a result of the construction of the Roticlot Dam in the border area of Indonesia and TimorLeste. The research used survey methods in Fatuketi Village, the location of agricultural infrastructure (Rotiklot Dam) in the Indonesia and Timor Leste Border Area. Data analysis uses Gini, Tobit ratios, and linear programming. The results of the Gini ratio analysis show that there has been a decrease in income inequality from medium (Gini Ratio = 0.44) to low (Gini Ratio = 0.26); and the results of the Tobit analysis state that the factor that has a significant positive effect on income inequality is land area, while farmer independence, the number of family dependents, and business capital have a significant negative effect. Furthermore, land resource factors that have a positive influence on income distribution are allocated appropriately and fairly so that income equality is achieved, namely IDR 3,732,692.81 (Gini Ratio = 0.00, which is a very low level of income inequality). It is recommended that agrarian reform through the distribution of additional land be adjusted to the existing conditions of land area, income, availability of water resources, and socio-economic factors.